Digitalisasi Perbankan Perspektif Fiqih - Albab, Ulil; Fatmah (Indonesian Proceedings and Annual Conference of Islamic Law And Sharia Economic (IPACILSE), 2023)
In this modern era, the development of digital technology extends to all sectors of life including banking. Banking digitization is a form of progress in digital transactions and is more preferred. This is because the method is very easy and practical. The purpose of this study is to find out digitalization in the perspective of fiqh. This research is a literature study, the method used in this research is normative legal research. The results of this study are, in a fiqh review, banking digitization is considered valid and sufficient, as long as the activity fulfills the terms and conditions of the transactions carried out. If the transaction makes it easier for someone, the syara' will recommend it, because the sharia itself wants convenience for its adherents